Cuentas por cobrar de la Empresa "Dismero" del Cantón Babahoyo, durante el Periodo 2022 – 2023. - Moran Villafuerte, Hamilton Emilio (2024)
This case study titled "Accounts Receivable of the 'Dismero' Company in the Babahoyo Canton during the Period 2022-2023" addresses the issue of inefficient management of accounts receivable in the Dismero company, which has affected its liquidity and financial stability. Justified by the need to identify and improve credit management processes, the study aims to examine financial information through the observation of financial statements, determine the origin of the increase in overdue credit portfolio by calculating financial indicators, and interpret the results obtained to understand the underlying causes of this increase. The methodology employed combines qualitative and quantitative approaches, utilizing the documentary review of financial statements and the calculation of key financial indicators. The results indicate a slight decrease in accounts receivable and provision for uncollectible accounts, suggesting improvements in debt recovery. However, challenges persist in the management of the credit portfolio, reflected in the stability of profit margins and a decrease in the return on assets and equity. The conclusions highlight the need to strengthen credit policies and improve collection strategies to optimize the management of accounts receivable, ensure liquidity, and strengthen the company's long-term financial viability.